Perception of postgraduate medical residents regarding educational environment at French Medical Institute for Mothers and children, Kabul Afghanistan - Nadeem Parpio, Yasmin; Farooq, Salima; Zahid, Nida; Abdul-Ghafar, Jamshid; Rehman, Rehana (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the perceptions of postgraduate medical education residents regarding educational environment at a medical institution in Afghanistan. Methods: The descriptive cross-sectional study was conducted from 2017 to 2018 at the French Medical Institute for Mothers and Children, Kabul, Afghanistan, FMIC, and comprised postgraduate medical residents. Dundee Ready Educational Environment Measure was administered to determine the perception of learning environment by the residents’ perceptions related to learning, teachers, academic self-perception, atmosphere and social self-perceptions sub scales. Data was analysed using SPSS 22. Results: Of the 63 subjects, 55(87.30%) were males and 42(66.66%) were married. The overall mean age was 30±4.38 years. There was no significant difference in mean subscales scores and overall scores in relation to participants’ age, gender, type of specialty, province and year of training (p>0.05). There was a significant difference in students’ perception of teachers in relation with the type of specialty (p<0.05). Conclusions: The educational environment at the medical institution in Afghanistan was perceived by the students of residency programme as conducive. Key Words: Dundee ready educational environmental measure, DREEM, Educational environment, Residency programme, Afghanistan.